Methodology to evaluate school buildings. Educational applications - Ros-Martín, Montserrat Irene (Advances in Building Education, 2021)
In this work, an innovative methodology to assess the security, habitability and functionality requirements of school buildings have been designed. The objectives are two: to design an evaluative methodology to assess technically the satisfaction of the basic requirements: safety, habitability and functionality that exist in public school buildings, and apply the methodology developed in university teaching so that students of the disciplines related to construction are able to justify, based on the regulations, their project decisions and intervention. The methodology is developed in the subject Applied Construction of the Master in Architecture of the Rey Juan Carlos University. The main result is that, from the detection of a real problem, such as the state of conservation of school buildings, we can developed an educational practice that helps Master students to ensure that their projects comply with current regulations. One of the most relevant conclusions is that the teaching applications of a real research, offer a provided value at academic level and a realistic view of the current constructions. Furthermore, stress the importance of both planning in accordance with the regulations and ensuring the conservation of the buildings